Changes in the nervous system which follow upon amputation of the limbs - Lowson, James Prain (The University of Edinburgh, 1911)
In this thesis I propose to give, in chronological order, an account of the observations recorded in the literature of my subject, to illustrate them by means of drawings from sections of the spinal cords of amputated patients and others;and, finally, to discuss the facts reported and the various theories which they have been held to support.

The drawings were made by me from sections which I prepared in the laboratory of Professor Marie in the Bicêtre Hospital at Paris. The drawings were produced by means of an apparatus which cast a magnified image of the section - stained by Weigert's method - upon the drawing sheet, so that its outlines could be readily and accurately reproduced. The reality of the scleroses demonstrated by the method of Weigert was confirmed by the subsequent staining of similar sections by the method of Van Giesen. To Professor Pierre Marie my thanks are due for his courtesy and kindness in supplying me with, the necessary material.